Balanced performance measurement in research hospitals: the participative case study of a haematology department - Simona Catuogno; Claudia Arena; Sara Saggese; Fabrizia Sarto (BMC, 2017)
Abstract Background The paper aims to review, design and implement a multidimensional performance measurement system for a public research hospital in order to address the complexity of its multifaceted stakeholder requirements and its double institutional aim of care and research. Method The methodology relies on a participative case study performed by external researchers in close collaboration with the staff of an Italian research hospital. Results The paper develops and applies a customized version of balanced scorecard based on a new set of performance measures. Our findings suggest that it can be considered an effective framework for measuring the research hospital performance, thanks to a combination of generalizable and context-specific factors. Conclusions By showing how the balanced scorecard framework can be customized to research hospitals, the paper is especially of interest for complex healthcare organizations that are implementing management accounting practices. The paper contributes to the body of literature on the application of the balanced scorecard in healthcare through an examination of the challenges in designing and implementing this multidimensional performance tool. This is one of the first papers that show how the balanced scorecard model can be adapted to fit the specific requirements of public research hospitals.